Teaching Paradigms: an Analysis of Traditional and Student-Centred Approaches - Tengku Kasim., Tengku Sarina Aini (Jurnal Usuluddin, 2014)
In the past, Malaysian educational system depends on didactic approach in teaching and learning that based on teachers’ instructions. However, in the era of globalization, educational system nowadays are progressing with regards to approach of teaching and learning at every level towards a more active and constructive education. This article examines traditional teaching approach paradigm which is teacher-centred and a new paradigm which is student-centred, in the context of Malaysian educational system, viewing from an Islamic educational perspective. It finds that this new paradigm could develop more active learners who have acquired the skills of problem-solving, independent thinking, and autonomous learning.